Gut Content Analysis of Labeo Calbasu at Different Seasons in Dekhar Haor, Sunamgonj, Bangladesh (American Journal of Agricultural Science, Engineering, and Technology, 2021)
This research was conducted to find out the seasonal (monsoon and post monsoon) variation in gut contents of Labeo calbasu from June to November, 2016 in Dekhar haor of Sunamgonj district, Bangladesh. Three orders of phytoplankton were identified from the gut content viz. Bacillariophyceae (11 genera), Chlorophyceae (9 genera), and Cyanophyceae (4 genera). Bacillariophyceae (6.98±1.61×103cell/L) were identified as the most dominant phytoplankton group. Two types of zooplankton viz. crustacean (5 genera) and rotifer (5 genera) were identified. Crustaceans (0.88±0.4×103cell/L) were identified as the dominant group among zooplankton. Feeding intensity (average index of fullness, Gastrosomatic index) was higher in the post monsoon season compared with the monsoon season. The findings concluded that L. calbasu prefers phytoplankton over zooplankton, and the plankton consumption was slightly higher in the post-monsoon season than in the monsoon season. This research is expected to be crucial in the management and conservation of endangered L. calbasu in open waters, as well as provide baseline work for future research and open the path for captive aquaculture.